Design science research applied to health technologies: A bibliometric analysis (Revista Contexto & Saúde, 2026)
This study aimed to identify and analyze the characteristics of scientific articles in the health field utilizing Design Science (DS) and Design Science Research (DSR) as research methods. A bibliometric search was conducted in the Web of Science Core Collection database on June 28, 2023. Two independent researchers reviewed and extracted data from the articles. VOSviewer software was employed for data description and quantitative evaluation. The search yielded 461 documents, of which 127 were included in the final analysis. DS and DSR methods were applied in 91% (n = 116) of the studies, addressing multidisciplinary areas (n = 88).  Most studies focused on health treatment/monitoring (n = 46), health management (n = 27), and mobile applications (n = 26). The findings suggest that integrating health technologies with DSR methods can provide a theoretical basis for innovative solutions in healthcare, health management, and governance.